Efficacy evaluation of acupuncture combined with manipulation for lateral epicondylitis: a meta-analysis - Jing Yin; Guangjun Tang; Baoli Zhao; Yuyang Zhang; Gang Bai; Liyong Liu; Chunli Chi; Wang Hongdong (Frontiers in Medicine, 2026)
Objective To systematically evaluate the efficacy of acupuncture combined with manipulation for relieving pain and improving function in patients with lateral epicondylitis (LE). Methods Randomized controlled trials (RCTs) involving patients with LE were retrieved from eight Chinese and English databases from inception to January 1, 2026. The risk of bias of the included studies was assessed using the Cochrane Risk of Bias tool. Meta-analysis was performed using RevMan 5.4.1 software. The main outcomes included clinical effectiveness, visual analog scale (VAS) score, Mayo elbow function score, and pain-free grip strength (PFG). Results Fourteen studies met the inclusion criteria. Meta-analysis showed that acupuncture combined with manipulation significantly improved clinical effectiveness (OR = 4.47, 95% CI: 2.8 to 7.14, p < 0.00001), Mayo elbow function score (MD = 7.51, 95% CI: 5.98 to 9.05, p < 0.00001), and PFG (MD = 2.88, 95% CI: 1.69 to 4.07, p < 0.00001). Compared with acupuncture alone (OR = 3.88, 95% CI: 1.95 to 7.73, p = 0.0001) or manipulation alone (OR = 4.94, 95% CI: 1.89 to 12.9, p = 0.001), the combined intervention was associated with higher clinical effectiveness. Subgroup analyses indicated that acupuncture combined with joint mobilization reduced pain (MD = −1.38, 95% CI: −1.63 to −1.13, p < 0.00001). Conventional acupuncture (MD = −0.88, 95% CI: −1.21 to −0.54, p < 0.00001) or moxibustion acupuncture (MD = −1.39, 95% CI: −1.65 to −1.12, p < 0.00001) combined with manipulation, as well as a 2-week treatment duration (MD = −1.31, 95% CI: −1.55 to −1.08, p < 0.00001), was associated with reduced VAS scores. Sensitivity analyses supported robustness of the pooled estimates, whereas funnel plots suggested potential publication bias. The certainty of the evidence was limited by risk of bias and substantial heterogeneity. Conclusion Current evidence suggests that acupuncture combined with manipulation may improve clinical effectiveness, elbow function, and pain-free grip strength in patients with lateral epicondylitis. However, the certainty of evidence is low due to high risk of bias and heterogeneity in the included studies. High-quality RCTs are needed to confirm these findings. Systematic review registration https://www.crd.york.ac.uk/PROSPERO/ , identifier: CRD42024572260.